2006
DOI: 10.1112/s0024610706023295
|View full text |Cite
|
Sign up to set email alerts
|

Real Hypersurfaces With Constant Principal Curvatures in Complex Hyperbolic Spaces

Abstract: We present the classification of all real hypersurfaces in complex hyperbolic space CH n , n 3, with three distinct constant principal curvatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 10 publications
0
74
0
1
Order By: Relevance
“…The Hopf real hypersurface which satisfies the previous conditions is that of type B in CH n . Substituting the eigenvalues of it in λ = −ν leads to a contradiction (for the eigenvalues see [1]). …”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hopf real hypersurface which satisfies the previous conditions is that of type B in CH n . Substituting the eigenvalues of it in λ = −ν leads to a contradiction (for the eigenvalues see [1]). …”
Section: Preliminariesmentioning
confidence: 99%
“…In [10], [11] Takagi was the first who studied and classified homogeneous real hypersurfaces in CP n and showed that they could be divided into six types, namely (A 1 ), (A 2 ), (B), (C), (D) and (E). In the case of CH n , Berndt in [1] classified real hypersurfaces with constant principal curvatures, when ξ is principal. Such real hypersurfaces are homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…These real hypersurfaces are Hopf ones with constant principal curvatures. In case of CH n , the study of real hypersurfaces with constant principal curvatures, was started by Montiel in [5] and completed by Berndt in [1]. They are divided into two types, namely (A) and (B), depending on the number of constant principal curvatures.…”
Section: Introductionmentioning
confidence: 99%
“…Those hypersurfaces have a lot of nice geometric properties (see Berndt [1] and Montiel and Romero [9]). In 2007 Berndt and Tamaru [2] classified all homogeneous real hypersurfaces in H n C.…”
Section: Introductionmentioning
confidence: 99%